Analisis Struktur Organisasi pada PT X - Balqis Shalah Munajah; Christian Wiradendi Wolor; Eka Dewi Utari (Jurnal Ilmiah Manajemen dan Akuntansi, 2025)
This study aims to analyze the organizational structure implemented at PT X. It focuses on understanding its role in supporting coordination and communication, identifying task distribution issues, and evaluating its effectiveness in achieving organizational goals. Using a descriptive qualitative method, the study highlights the importance of a well-structured organization in facilitating decision-making, enhancing work efficiency, and streamlining communication channels. Findings reveal that although PT X has a formal organizational structure, its practical implementation encounters challenges. These include unclear task assignments, overlapping roles, workload imbalance, and slow cross-division communication. A lack of periodic structural evaluations further reduces operational efficiency. To overcome these problems, PT X must refine task distribution, clarify reporting lines, and improve interdepartmental coordination. The study concludes that an effective organizational structure requires consistent, adaptive, and integrated implementation aligned with the dynamic needs of the organization.